Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s1368980020002803
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patterns of weight change 1 year after delivery in a cohort of Mexican women

Abstract: Objective: To evaluate the associations of pregestational BMI, gestational weight gain (GWG) and breast-feeding at 1 month postpartum with four patterns of weight change during the first year after delivery: postpartum weight retention (PPWR), postpartum weight gain (PPWG), postpartum weight retention + gain (PPWR + WG) and return to pregestational weight. Design: In this secondary analysis of a prospective study, we categorised postpartum weight change into four patterns using pregestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Nineteen countries were represented. Fourteen studies took place in North America, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] six in Europe, [44][45][46][47][48][49][50][51] four in Australia, [52][53][54][55] seven in East/ Southeast Asia, 27,[56][57][58][59][60][61] one in Turkey, 28 1 in Lebanon/Qatar, 62 and one in Brazil. 63 The mean age of participants ranged from 23.8 to 33.3 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen countries were represented. Fourteen studies took place in North America, [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] six in Europe, [44][45][46][47][48][49][50][51] four in Australia, [52][53][54][55] seven in East/ Southeast Asia, 27,[56][57][58][59][60][61] one in Turkey, 28 1 in Lebanon/Qatar, 62 and one in Brazil. 63 The mean age of participants ranged from 23.8 to 33.3 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…29,33,35,42,46,51 Socioeconomic status (SES) of women varied across studies. Six studies comprised predominantly women with low SES, defined as low educational attainment and/or low income, 30,32,33,40,41,56 whereas two studies reported that about half of the women in their cohort had low SES status. 29,37 Only primiparous women were recruited for four studies, 27,31,34,36,43 whereas one study recruited only multiparous women.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Breastfeeding confers many benefits to not only the child but the mother as well [ 9 , 10 ], such as reduced risk of type 2 diabetes, certain breast cancers, and ovarian cancer [ 11 , 12 ]. Recent research has examined breastfeeding’s association with postpartum weight retention with breastfeeding characterized in various ways including duration (months or weeks) or ever breastfeeding [ 13 , 14 ]. However, it is unknown whether effects of breastfeeding duration on weight retention and long-term body size vary by socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%